The Influence of Internship Effectiveness on Graduate Employability Skills of Undergraduate Business Administration Students at a Private University in Thailand - Aung, Yu Mon Mon; Asavisanu, Poonpilas (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
Internships for business students need to be effective as they play an important role in preparing students for the workforce. This quantitative study aimed to investigate the influence of Internship Effectiveness, as defined by Academic Preparedness, Positive Attitude, Self-initiative, Challenging Tasks, Effectiveness of Supervision, Task Clarity, and Compensation, on Graduate Employability Skills of undergraduate business administration students at a private university in Thailand. The Model of Internship Effectiveness and CareerEDGE Model of Graduate Employability guided as the theoretical framework. Data was collected through a self-reported questionnaire adopted from Phoebe (2010) and Dacre Pool et al. (2014) and a convenience population sample of 72 students participated. Descriptive statistics (mean and standard deviation) and multiple linear regression analysis was employed. Findings revealed moderately high levels of both internship effectiveness and graduate employability skills. While Academic Preparedness, Positive Attitude, and Effectiveness of Supervision, were positively correlated with Graduate Employability Skills, these correlations were not strong enough to have significant, predictive linear relationships. Self-initiative and Task Clarity demonstrated significant, positive predictive relationships with Graduate Employability Skills, explaining 76.1% of the variance. An inverse relationship was found for Compensation that belonging to certain compensation group is associated with lower predicted Graduate Employability Skills, however, the differential effect was not significant. These findings show that by prioritizing Self-initiative and Task Clarity during internships, these aspects can enhance undergraduate business administration students’ Graduate Employability Skills in this context.